Non-targeted Metabolomics Analysis Based on LC–MS to Assess the Effects of Different Cold Exposure Times on Piglets - Chen, Yong; Ji, Hong; Guo, Jingru; Chen, Yan; Li, Wenjie; Wang, Shengping; Zhen, Li (Frontiers in Physiology, 2022)
Pigs are susceptible to low temperature conditions, and cold stress causes metabolic changes in the body to increase heat production as an adaption to adverse environments. To characterize and validate different metabolites in piglet livers at different cold exposure times, sixteen 30-day-old male weaned piglets with similar weights were randomly divided into four groups: the normal temperature group (24 ± 2°C, NT) and cold exposure (4 ± 2°C) 2-h group (CS2), 6-h group (CS6), and 12-h group (CS12). At the end of the experiment, the liver samples were analyzed using systemic non-targeted metabolomics. Eight known differentially abundant metabolites (farnesyl pyrophosphate, isocitrate, triethanolamine, phenylethylamine, deoxynosine, citric acid, maltotriose, and epinephrine) were observed between the CS groups and the control group in positive and negative ion modes. The eight main differentially abundant metabolites involved in seven metabolite classifications. Metabolic pathways and enrichment analyses revealed that the pathways involved three KEGG pathway classifications. Most of the pathways were related to amino acid or energy metabolism. Moreover, the metabolic pathways were not identical under different cold exposure times, with those following 2 and 6 h of cold exposure more related to carbohydrates and energy production and those following 12 h of cold exposure more related to the metabolism connected with epinephrine. Thus, under different cold exposure times, the metabolite profiles and metabolic pathways differed.